About game meat on Polish tables in the second half of the 19th century - Hubicki, Piotr; Studnicka-Mariańczyk, Karolina (Perspektywa stołu, 2023)
Game meat has been an important component of human food for centuries. Eating it itself has been part of the traditions of many social strata throughout history. Each social group in the 19th century used game in a different way. For peasants, game was an opportunity to survive or earn money quickly, while on the tables of landed gentry it was often served and was one of the most important ingredients of the menu. The authors of the article paid attention to the issue of acquiring game, the appearance of the hunt and which animals were hunted by hunters. Game farms, i.e. methods of breeding forest animals, were described, as well as the issue of distribution of venison. It then discusses methods of preparing the meat. The final part of the work is devoted to the description of specific venison dishes based on 19th century cookbooks and family and estate archives. Preparing and eating meals can be a very prosaic activity, serving only to satisfy hunger, to fulfil one of the basic physiological needs. A meal may also take the form of a special celebration - marked by the abundance and elaborate preparation of individual dishes, their ceremonial serving at the table. The authors have therefore mainly paid attention to how and in what form venison was consumed in the second half of the 19th century.